Information Technology Capability and Firm Performance in The Era of Big Data Analytics: Evidence from The United States - Jahidur Rahman; Ning Zhao (Journal of Accounting and Management Information Systems (JAMIS), 2020)
Research Question: This study investigates the relationship between information technology (IT) capability and firm performance in the 2010s, the era of big data analytics (BDA), in the context of US companies. Motivation - With the evolution of business intelligence and the proliferation of analytic tools that further improve IT capability, it is more important than ever to understand whether firms with stronger IT capabilities perform better. Idea - After categorizing firms into pairs of IT leaders and control groups, the performance of each pair of firms in each group was compared. Data - All data are publicly available from Compustat and InformationWeek (IW) 500. Tools - The Wilcoxon signed-rank test and regression analysis were used to examine how the performance of IT leaders and control groups changed during the 2010–2017 period. Findings - This results show no significant relationship between a firm's IT capability and its performance in the sample of US companies during this period. Contribution - This study will help academicians and practitioners to better understand how the adoption and application of BDA derived from IT capability affects firm performance.
Keywords: M41; L25; 650; Big data analytics (BDA); information technology (IT) capability; firm performance; IW 500; IT business value